ASSESSMENT OF THE QUALITY OF LIFE OF PATIENTS AFTER RADICAL CYSTECTOMY PERFORMED BY EXTRAPERITONEAL ACCESS - Mirzagalib N. Tillashayxov; Mashrabjon I. Boltayev; Jalol H. Mirhamidov (Central Asian Journal of Medicine, 2024)
Objective: to evaluate the quality of life of patients with invasive bladder cancer after undergoing radical cystectomy performed through extraperitoneal access. Material and methods: 90 patients with invasive bladder cancer stage T2-3N0-2M0, aged 63.2±4.3 years, were examined. All patients underwent radical cystectomy using an extraperitoneal approach with dissection of the pelvic lymph nodes. Surveillance monitoring was carried out when the patient was discharged from the hospital, 3 and 12 months after surgery. To assess the quality of life of patients, the SF-36 and KDQOL-SF™ 1.3 questionnaires were used. Results: When performing radical cystectomy via extraperitoneal access in the early stages of the postoperative period, a predominance of average scores on the SF-36 and KDQOL-SF™1.3 questionnaires was established. In the long-term postoperative period after 12 months, the patient’s general health is completely restored and the quality of life significantly improves. Conclusion: SF-36 and KDQOL-SF™1.3 questionnaires. allow us to objectively assess the impact of radical cystectomy on the quality of life of patients at different times after surgery.